Decreasing complications of pectoralis major muscle flap reconstruction with two modalities of negative pressure wound therapy. (February 2022) - Myllykangas, Heidi-Mari; Halonen, Jari; Husso, Annastiina; Berg, Leena T.
Background and objective: Deep sternal wound infection is a feared complication of open-heart surgery. Negative pressure wound therapy has gained an important role in the treatment of deep sternal wound infection. Incisional negative pressure wound therapy has been introduced as a method to prevent wound complications after sternotomy, and lately, after flap reconstructions in the treatment of deep sternal wound infection. We aimed to study if incisional negative pressure wound therapy with PICO™ had similar beneficial effect described earlier with competing commercial devices. Methods: This study included 82 patients treated with pectoralis major muscle flap for deep sternal wound infection during the years 2006–2020. PICO group consisted of 24 patients treated with preoperative negative pressure wound therapy and postoperative incisional negative pressure wound therapy (PICO™). Two control groups included 48 patients with conventional treatment and 10 patients with preoperative negative pressure wound therapy only. Results: In the PICO group, the complication rate declined from 50.0% to 33.30%, major complication rate from 29.2% to 12.5%, and need for an additional flap from 14.6.% to 4.2% when compared to conventional treatment. The length of hospital stay decreased as well. Preoperative negative pressure wound therapy alone was associated with moderate decline in the complication rates. In addition, we described the use of split pectoralis major muscle flap reconstruction in 57 patients. To our knowledge, this is the largest published patient series describing this method in the treatment of deep sternal wound infection. Conclusions: Incisional negative pressure wound therapy with PICO™ seems beneficial after flap reconstruction. Split pectoralis major muscle flap is a versatile reconstruction option suitable to be used as a workhorse in the treatment of deep sternal wound infection.